Film breakdown onset Reynolds number of an absorption heat transformer with falling film heat exchangers: Modeling and estimation. (October 2022) - Canela-Sánchez, I.J.; Juarez-Romero, D.; Huicochea, J.A.; Escobar-Jiménez, R.F.; Delgado-Gonzaga, J.; Esche, E.; Repke, J.-U.
Abstract: This work presents the development of a physical model for an absorption heat transformer with falling film heat exchangers. The absorption heat transformers are devices for increasing moderate temperatures of heat sources to more useful levels to be used in some processes as water purification. The process units are modeled in lumped form to reduce the model complexity. The phenomena that appear in the falling film heat transfer are analyzed. The laminar flow with partial wetting describes the behavior of the units. The falling film reaches full wetting efficiency at the film breakdown onset Reynolds number, which is considered a parameter. Sensitivity analysis is applied to the AHT model to identify the sensible variables that are affected by the film breakdown onset Reynolds number of each unit, then these parameters are estimated. The film breakdown onset Reynolds number estimated for the units are from 8.90 to 141.28, which depend on the unit geometries, the fluid properties, and the physical phenomenon. The evaporator lumped model of the process of this work is compared with a detailed evaporator model specific regarding each round of coil presented in previous research. From this comparison, it is recommended to model the first tube of the evaporator individually while the other tubes can be modeled in lumped form. The model results are compared with experimental results to validate the model. The comparison shows low errors from 0.22 to 6.13 %, except for the pressure of the evaporator–absorber chamber with an error of 13.83 %. Finally, some tests at different generator temperatures varying the cooling water temperature from 33.8 ° C to 31.8 ° C decrease the pressure by approximately 0.53 kPa and increase the flow of refrigerant by 0.00011 kg/s. The establishment of the model and the estimation of the unknown parameters would contribute to the development of accurate dynamic models for absorption heat transformers to implement strategies to improve control process. Highlights: The film breakdown onset Reynolds number affects the heat transfer rate. The film breakdown onset Reynolds numbers estimated are from 8.90 to 141.28. The effect of cooling water temperature on pressure and generated vapor is analyzed. Model description of desorption, condensation, evaporation, and absorption.